Chronic intestinal pseudo-obstruction as an expression of inflammatory enteric neuropathy - Pimentel,Rita (2014)
Background Chronic intestinal pseudo-obstruction (CIPO) is characterised by inadequate digestive tract motility and can lead to severely disordered motility. CIPO manifests as recurrent episodes of intestinal sub-occlusion without an anatomical obstruction. We present the case of a 41-year-old female, with severe chronic constipation and several episodes of intestinal sub-occlusion. Investigation revealed colonic inertia and marked distension of the small bowel and colon with no evidence of stenosis or obstructive lesions, compatible with CIPO. After several treatments were tried (domperidone, erythromycin, cisapride, octreotide, total enteral nutrition), with partial or no response, further work-up was done trying to identify an etiology. Gastrointestinal manometry showed neuropathic type abnormalities, transmural biopsy of the jejunum revealed degenerative enteric neuropathy and anti-HU antineuronal antibody screen was positive, suggesting an autoimmune type neuropathy with diffuse involvement of the digestive tract. Corticosteroids showed partial improvement of short duration and azathioprine was also tried but discontinued due to intolerance. Marked dietary intolerance and malnutrition lead to total parenteral nutrition (TPN) at home since October 2011. Since then, symptoms and nutritional status improved, with rare episodes of pseudo-obstruction, not requiring hospitalisation.